2017
DOI: 10.7196/ajhpe.2017.v9i3.881
|View full text |Cite
|
Sign up to set email alerts
|

Registrar wellness in Botswana: Measuring burnout and identifying ways to improve wellness

Abstract: Background. Burnout during registrar training is high, especially in resource-limited settings where stressors are intensified. Burnout leads to decreased quality of life for doctors, poor job and patient satisfaction, and difficulty retaining doctors. Objectives. Primary: to measure burnout among registrars working at Princess Marina Hospital in Gaborone, Botswana. Secondary: to determine factors contributing to burnout and identify potential wellness interventions. Methods. The validated Maslach Burnout Inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 18 publications
(67 reference statements)
0
6
0
Order By: Relevance
“…Work-related mental health issues studied included physical violence by patients, 54 burnout among registrars, 55 perceived stress and performance appraisal discomfort among managers 56 and occupational stress among university secretaries. 57…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Work-related mental health issues studied included physical violence by patients, 54 burnout among registrars, 55 perceived stress and performance appraisal discomfort among managers 56 and occupational stress among university secretaries. 57…”
Section: Resultsmentioning
confidence: 99%
“…53 Work-related mental health issues. Work-related mental health issues studied included physical violence by patients, 54 burnout among registrars, 55 perceived stress and performance appraisal discomfort among managers 56 and occupational stress among university secretaries. 57 One study reported healthcare workers' lifetime experience of physical violence from patients, which was associated with greater job dissatisfaction.…”
Section: Areas Of Mental Health Addressed In the Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Employees are further dissatisfied and demotivated by inadequate public performance management systems (Bester & Hofisi, 2020) and insufficient total reward models (Tshukudu, 2020). Consequently, staff members are at risk of developing high levels of stress and burnout, resulting in detachment from their jobs and institutions (Dubale et al, 2019;Westmoreland et al, 2017). High burnout and organisational detachment undermine public service efficiency (Eldor, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the article by Westmore land et al [7] examines the improvement of the learning environment and wellness of trainee regis trars to prevent burnout and exhaustion, while Urimubenshi et al [8] explore solutions from students' perceptions on how to improve their learning environment. The article by Jacobs and Venter [9] speaks to improving the clinical learning environment using standardised patient simulation.…”
mentioning
confidence: 99%